Pedicled buccal fat pad for the augmentation of facial depression deformity: A case report. Issue 30 (July 2017) - Komatsu, Seiji; Ikemura, Kou; Kimata, Yoshihiro
Abstract: Rationale: Tissue augmentation of facial depression deformities can be achieved by volume replacement with autologous fat injection, dermal filler injection, etc. Here, we report a case of tissue augmentation of a facial depression deformity using a pedicled buccal fat pad (BFP). Patient concerns: A 64-year-old woman was referred with a chief complaint of facial depression deformity. Diagnoses: Her molars had been removed at another hospital 12 years prior to this referral, and the patient suffered from a left cheek depression deformity as a sequela of a postextraction infection. Interventions: An incision was made in the left gingivobuccal sulcus under local anesthesia, and BFP was carefully excised from its normal location. The subcutaneous scar tissue was dissected, and a pocket was created via the same mucosal incision. BFP was then pushed into the pocket. Outcomes: The depression deformity immediately disappeared postoperatively. The transplanted BFP remained unabsorbed and soft 43 months postoperatively. The patient did not have any complications. Lessons: This novel procedure has 2 advantages. First, the pedicled BFP is a vascularized tissue and is not absorbed postoperatively; control of contour is easy, and only 1 treatment session is required. Complications associated with fat necrosis can be avoided. Second, only a single intraoral incision is required; the risk of donor-site morbidity is very low, and scar formation does not occur on exposed skin. Third, this procedure can be performed without special instruments and equipment. The main disadvantages are limited rotation arc and volume of pedicled BFP. Despite its limited application, this procedure is simple and useful, with low invasiveness.